Synthesis, Properties and Applications of Lanthanide and Actinide Molecular Compounds - Leonor Maria; Joaquim Marçalo (Inorganics)
Lanthanides and actinides have unique physical and chemical properties, and their compounds continue to be extensively studied on a fundamental level during the search for applications that range from energy production and related environmental issues to the life sciences [...]